Snapshot of Adaptive Management in Peacebuilding Programs - and Queen, Emily Forsyth; Baumgardner-Zuzik, Jessica; Hume, Elizabeth; Greenberg, Melanie (Alliance for Peacebuilding, 2018)
The Alliance for Peacebuilding developed the report Snapshot of Adaptive Management in Peacebuilding Programs with support from Humanity United. This report examines how existing organizational programs are designing and learning from adaptive management in a conflict effected and fragile states. It further provides practical recommendations for applying adaptive management to peacebuilding programs based on synthesis … Continue reading "Snapshot of Adaptive Management in Peacebuilding Programs"
Keywords: KEY